The Information Technology Model for Customer Relationship Management - Yingmuang, Sompong (JOURNAL OF SOUTHERN TECHNOLOGY, 2018)
The purpose of this research was to develop an information technology model for customer relationship management (ITCRM). The sample was a resort located in Hua Hin, Prachuap Khiri Khan Province. The tool was a set of questionnaires. The data were analyzed employing percentage, mean, and Chi-square. The results were obtained. 1) The efficiency of information technology model for customer relationship management applying the Kendall Coefficient of Concordance was approved and accepted as an efficient model by experts. The consistent acceptance was made from the statistical significance of 0.01. 2) The test of satisfaction for customer relationship management model was made by the resort personnel and more than 90% of them revealed to be satisfied with the model at a high and highest level with statistical significance of 0.01. 3) More than 90% of the clients felt very satisfactory, or at a high and highest level with statistical significance of 0.01. The contribution in this research is ITCRM model and the development process quality for thoroughly checking in all steps. The model was developed and integrated into a new innovation and could be applied with information technology model for customer relationship management.